The Effect Of Perceived Benefits And Ease Of Use On Interest In Using Gopay As A Digital Payment Service In Bengkulu City - Lestari , Tri; Soleh, Ahmad; E.G , Ida Ayu Made (Universitas Dehasen Bengkulu, 2026)
Advances in information and communication technology have driven innovation in the financial sector, such as financial technology (fintech), particularly digital payment services or e-wallets. In Indonesia, the use of e-wallets has grown rapidly, with GoPay and OVO as the two most dominant platforms. E-wallets facilitate various transactions for the public, such as online shopping, bill payments, and money transfers. Based on the Technology Acceptance Model (TAM) theory, interest in using e-wallets is influenced by users' perceptions of convenience and benefits. The purpose of this study is to determine the effect of perceived benefits and ease of use on interest in using GoPay as a digital payment service in Bengkulu City. The method used in this study is quantitative, and the sample consists of GoPay users in Bengkulu City, with a sample size of 130 respondents.The results of this study indicate that the variables of perceived benefits and ease of use have a significant effect on the interest in using GoPay as a digital payment service in Bengkulu City, both partially and simultaneously.